2021
DOI: 10.1007/s40333-021-0052-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of a large-scale remote sensing ecological index in arid areas and its application in the Aral Sea Basin

Abstract: The Aral Sea Basin in Central Asia is an important geographical environment unit in the center of Eurasia. It is of great significance to the ecological protection and sustainable development of Central Asia to carry out dynamic monitoring and effective evaluation of the eco-environmental quality of the Aral Sea Basin. In this study, the arid remote sensing ecological index (ARSEI) for large-scale arid areas was developed, which coupled the information of the greenness index, the salinity index, the humidity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 48 publications
(44 reference statements)
1
29
0
Order By: Relevance
“…The combined use of geospatial technologies and AHP in zoning LDV areas enhances the decision-making process and provides better accuracy on a regional to local scale [3,16]. Previous case studies demonstrated that the integration of geospatial technologies and AHP proved successful in assessing LDV in many desert areas worldwide, such as in China [12], Iraq [32], and the Aral Sea basin in Central Asia [33].…”
Section: Introductionmentioning
confidence: 99%
“…The combined use of geospatial technologies and AHP in zoning LDV areas enhances the decision-making process and provides better accuracy on a regional to local scale [3,16]. Previous case studies demonstrated that the integration of geospatial technologies and AHP proved successful in assessing LDV in many desert areas worldwide, such as in China [12], Iraq [32], and the Aral Sea basin in Central Asia [33].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, I wet was chosen as the humidity index [28], which is expressed as land surface moisture and is generated from Landsat TM, ETM+ and OLI image reflectance using Equations ( 1)-( 3) [10,23,29]:…”
Section: Study Area and Data Preprocessingmentioning
confidence: 99%
“…Using the RSEI will help in studying the interactions between human activities and natural ecology, and the resulting knowledge of theory, concepts and methods is expected to benefit local governments [20]. In recent years, the RSEI has been applied in ecological quality monitoring in 35 cities of China [19,21,22], Eurasia [23] and America [21,23]. The RSEI and the results of principal component analysis (PCA) have been combined to develop an ecological index [19,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More in-depth studies have been carried out on the shrinkage of the Aral Sea [22][23][24], the microbiome of the Aral Sea [25][26][27], and the ecological environment of the basin [28][29][30][31][32]. The research on lake sediments has become more abundant, e.g., environmental reconstructions of the salt water, geological structure, etc.…”
Section: Introductionmentioning
confidence: 99%